Coagulase-negative staphylococci (CoNS) meningitis: a narrative review of the literature from 2000 to 2020. (September 2020) - Azimi, T.; Mirzadeh, M.; Sabour, S.; Nasser, A.; Fallah, F.; Pourmand, M.R.
Abstract: Coagulase-negative staphylococci (CoNS) are recognized as comprising the main part of human normal microbiota and are rarely associated with severe and intensive infections. However, these organisms can cause a number of infections in humans, especially immunocompromised patients and neonates. Bacterial meningitis, as an important and acute infection in the central nervous system, is still a major global health challenge and a serious infectious disease, causing a high rate of mortality and morbidity. CoNS as causative agents of meningitis are generally related to trauma or direct implantation of foreign bodies and the presence of a cerebrospinal fluid shunt. Numerous epidemiologic and clinical studies have shown that different CoNS isolates such as Staphylococcus capitis, Staphylococcus lugdunensis, Staphylococcus hominis, Staphylococcus epidermidis, Staphylococcus schleiferi, Staphylococcus saprophyticus, Staphylococcus warneri and Staphylococcus haemolyticus are more frequently associated with meningitis. This study attempts to determine the role of CoNS in meningitis and reviews the reported cases of meningitis induced by CoNS from the year 2000 to 2020 in the literature.